Key Roles of Hyaluronan and Its CD44 Receptor in the Stemness and Survival of Cancer Stem Cells - Chanmee, Theerawut (Front Oncol, 2015)
Cancer stem cells (CSCs) represent a unique subpopulation of self-renewing oncogenic cells that drive cancer initiation and progression. CSCs often acquire multidrug and oxidative stress resistance and are thereby thought to be responsible for tumor recurrence following treatment and remission. Although the mechanisms responsible for CSC generation, maintenance, and expansion have become a major focus in cancer research, the molecular characteristics of CSCs remain poorly understood. The stemness and subsequent expansion of CSCs are believed to be highly influenced by changes in microenvironmental signals as well as genetic and epigenetic alterations. Hyaluronan (HA), a major component of the extracellular matrix, has recently been demonstrated to provide a favorable microenvironment for the self-renewal and maintenance of stem cells. HA directly and indirectly affects CSC self-renewal by influencing the behavior of both cancer and stromal cells. For instance, HA in the tumor microenvironment modulates the function of tumor-associated macrophages to support CSC self-renewal, and excessive HA production promotes the acquisition of CSC signatures through epithelial-to-mesenchymal transition. The importance of HA in mediating CSC self-renewal has been strengthened by the finding that interactions between HA and its receptor, CD44, propagate the stemness of CSCs. HA–CD44 interactions evoke a wide range of signals required for CSC self-renewal and maintenance. CD44 also plays a critical role in the preservation and multidrug resistance (MDR) of CSCs by transmitting survival and anti-apoptotic signals. Thus, a better understanding of the molecular mechanisms involved in HA and CD44 control of CSC stemness may help in the design of more effective therapies for cancer patients. In this review, we address the key roles of HA and CD44 in CSC self-renewal and maintenance. We also discuss the involvement of CD44 in the oxidative stress and MDR of CSCs.